Review of energy demands and wind resource assessment of the Solovetsky Archipelago - Ghani, Rizwan; Virk, Muhammad Shakeel; Kangash, Aleksei; Maryandshev, Pavel; lubov, viktar; Mustafa, Mohamad (International Journal of Smart Grid and Clean Energy, 2019)
Published version available at: http://www.ijsgce.com/index.php?m=content&c=index&a=show&catid=81&id=471 This paper aims to analyse the current situation of the energy system of the remote island territory of Solovetsky Archipelago. The Solovetsky historical and cultural complex was included in the list of UNESCO World Heritage Sites. Diesel fuel, which is used on the archipelago is expensive and pollutes the environment. By using Computational Fluid Dynamics (CFD) based numerical method, this study aims to determine the wind energy potential of the territory, which will cover part of the energy consumption. For the best use of wind potential, several variants of the location of the wind park were analyzed in this study. Thus, using wind energy, as an alternative source, the amount of emissions of harmful substances will be reduced, which is a priority for the Arctic region.